Analysis of the Effect of Credit Restructuring on the Liquidity Level of Banks Listed on the Indonesian Stock Exchange (IDX) Before and After the COVID-19 Pandemic - Rahmatulloh, Muhammad Wilszam; Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effect of credit restructuring on liquidity levels through the Loan to Deposit Ratio before the COVID-19 pandemic and after the COVID-19 pandemic. The data used is secondary data in financial reports for 2019 before the COVID-19 pandemic and 2020-2023 after the COVID-19 pandemic. The results of this research show that the Loan to Deposit Ratio experienced a decrease, as evidenced by the results of descriptive statistical research, which showed the average difference (Loan to Deposit Ratio decreased by 0.1423.